KAT7-acetylated YBX1 promotes hepatocellular carcinoma proliferation by reprogramming nucleotide metabolism - He Huang; Longfei Ren; Yongqiang Zhou; Pengyu Chen; Haixia Zhao; Shang Li; Haiping Wang; Xun Li (BMC Cancer)
Abstract Background Lysine acetylation is a critical post-translational modification regulating tumor initiation and progression. Lysine acetyltransferase 7 (KAT7)-mediated lysine acetylation is frequently dysregulated in cancer. However, the role of KAT7-mediated lysine acetylation in hepatocellular carcinoma (HCC) progression remains unclear. Methods Bioinformatic analysis was used to investigate the expression, clinicopathological characteristics and diagnostic prognostic value of KAT7 in HCC. CCK-8 assays, colony-forming assays, apoptosis assays and nude mouse xenograft models were utilized to detect the oncogenic functions of KAT7 in HCC. Immunoprecipitation (IP) assay and mass spectrometry (MS) analysis were performed to identify the KAT7-binding protein Y-box binding protein 1 (YBX1). Transcriptome sequencing and functional enrichment analysis were employed to elucidate the downstream pathway regulated by KAT7 and YBX1. Chromatin immunoprecipitation (ChIP) assay was used to evaluate YBX1 binding to the promoter regions of ribonucleotide reductase regulatory subunit M2 (RRM2) and thymidine kinase 1 (TK1). Weighted gene co-expression network analysis and selection operator regression analysis were used to build risk prediction models. Results This study demonstrated that elevated KAT7 expression is associated with poor prognosis in HCC patients. Knockdown of endogenous KAT7 in HCC cells attenuated tumorigenic phenotypes associated with cell proliferation, colony formation and orthotopic xenograft tumor growth, indicating a pro-tumorigenic role of KAT7 in HCC. YBX1 was identified as a novel non-histone substrate for KAT7, and the E508 residue of KAT7 is essential for binding. Following the functional enrichment analysis, KAT7 and YBX1 were correlated with nucleotide metabolism. Furthermore, KAT7 binds to YBX1 and modulates its post-translational expression, which enhances the transcriptional activity of the central nucleotide metabolism enzymes RRM2 and TK1. Additionally, we constructed a novel prognostic prediction model based on KAT7, YBX1, RRM2 and TK1, which validated the predictive accuracy and prognostic value of KAT7-mediated acetylation is consistent with clinical outcomes in HCC. Conclusions Our findings highlight that KAT7 acetylates YBX1 and promotes HCC progression by reprogramming nucleotide metabolism, offering therapeutic implications.